Integrasi Sistem Kendali Beban Listrik dan Absensi Berbasis RFID untuk Efisiensi Energi di Lingkungan Perguruan Tinggi. - Oktrison; Ade Chairullah; Ester Edwar; Erwin Sipahutar (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Electricity constitutes a fundamental and indispensable resource within higher education institutions, as a substantial majority of both academic and administrative operations are profoundly dependent on electrical energy. Given the persistent escalation in electricity tariffs and the increasing proliferation of electrical devices, there exists a pressing necessity for technological innovations that facilitate energy conservation and enhanced efficiency. This research endeavor seeks to devise and implement a system that fosters optimal electricity utilization by amalgamating RFID-based technology with an automated attendance detection framework. The system functions autonomously by documenting attendance through the identification embedded in the national e-KTP chip, which concurrently unlocks the classroom door and activates electrical devices such as illumination, air conditioning units, and projectors. The findings of the research demonstrate a 100% efficacy in device functionality and an approximate annual electricity conservation of IDR 3,000,000 per room. This system represents a promising technological advancement for improving energy efficiency while simultaneously contributing to the digital metamorphosis of academic services within universities